THE EFFECT OF TRANSFER PRICING, INTANGIBLE ASSETS AND CAPITAL INTENSITY ON TAX AGGRESIVENESS WITH FOREIGN OWNERSHIP AS A MODERATING VARIABLE - Sudaryono, Driya; Murwaningsari, Etty (CV. Radja Publika, 2023)
For the government, taxes are a source of state revenue. However, for companies, taxes are considered a burden that can reduce their profits. This difference can potentially cause non-compliance by taxpayers and has implications for corporate efforts to carry out tax aggressiveness. This study determines the effect of transfer pricing, intangible assets, and capital intensity on tax aggressiveness with foreign ownership as a moderating variable. This study uses data from manufacturing companies listed on the Indonesia Stock Exchange (IDX) in a sample of 36 companies with 108 observations during the 2018-2020 period. The results show that both transfer price and intangible assets positively affect tax aggressiveness, while capital intensity does not affect tax aggressiveness. Foreign ownership was found to strengthen the effect of transfer prices and intangible assets on tax aggressiveness. Furthermore, foreign ownership does not strengthen the effect of capital intensity on tax aggressiveness. Keywords: transfer price, intangible assets, capital intensity, foreign ownership, tax aggressiveness